Overexpression of an Apocynum venetum DEAD-Box Helicase Gene (AvDH1) in Cotton Confers Salinity Tolerance and Increases Yield in a Saline Field - Chen, Jie; Wan, Sibao; Liu, Huaihua; Fan, Shuli; Zhang, Yujuan; Wang, Wei; Xia, Minxuan; Yuan, Rui; Deng, Fenni; Shen, Fafu (Frontiers in Plant Science, 2016)
Soil salinity is a major environmental stress limiting plant growth and productivity. We have reported previously the isolation of an Apocynum venetum DEAD-box helicase 1 (AvDH1) that is expressed in response to salt exposure. Here, we report that the overexpression of AvDH1 driven by a constitutive cauliflower mosaic virus-35S promoter in cotton plants confers salinity tolerance. Southern and northern blotting analyses showed that the AvDH1 gene was integrated into the cotton genome and expressed. In this study, the growth of transgenic cotton expressing AvDH1 was evaluated under saline conditions in a growth chamber and in a saline field trial. Transgenic cotton overexpressing AvDH1 was much more resistant to salt than the wild-type plants when grown in a growth chamber. The lower membrane ion leakage, along with increased activity of superoxide dismutase (SOD), in AvDH1 transgenic lines suggested that these characteristics may prevent membrane damage, which increases plant survival rates. In a saline field, the transgenic cotton lines expressing AvDH1 showed increased boll numbers, boll weights and seed cotton yields compared with wild-type plants, especially at high soil salinity levels. This study indicates that transgenic cotton expressing AvDH1 is a promising option for increasing crop productivity in saline fields.